Evaluation of Mechanical Performance of Compacted Magnesium Hydroxide after Carbonation Curing - Akca, Abdullah Huzeyfe; Ma, Siwei; Esposito, Daniel; Kawashima, Shiho (ASCE-AMER SOC CIVIL ENGINEERS, 2022)
In this study, the potential to directly use magnesium hydroxide as an alternative binder was investigated. A compaction molding technique was employed, where magnesium hydroxide powder was mixed with water at relatively low water-to-binder ratios, compacted in a mold, then subjected to accelerated CO2 curing at room temperature to form a carbonate binder. The influence of water-to-binder ratio and compaction pressure on the mechanical and microstructural properties of compacted magnesium hydroxide systems under accelerated CO2 curing was evaluated. Results showed that compaction pressure and water-to-binder ratio have a significant effect on CO2 uptake and strength development. An optimum compaction level was found to be 3 MPa in this study, where compressive strengths of 33.5 +/- 4.0 and 70.8 +/- 4.1 MPa were reached after 2 and 5 days of CO2 curing. Results highlight the potential to tailor the mechanical properties of magnesium hydroxide systems through processing, and to reach strengths comparable to those of magnesium oxide systems but with the advantage of skipping the calcination step and reducing water demand. (C) 2022 American Society of Civil Engineers.
Keywords: Magnesium hydroxide; Cement; Compaction; Carbonation; Early age strength; Microstructure; LIFE-CYCLE ASSESSMENT; REACTION-KINETICS; CONCRETE; BINDERS; EMISSIONS; DYPINGITE; DESIGN; ENERGY; Construction & Building Technology; Engineering; Materials Science